Preliminary Findings of a Four-Session Psychoeducational Group for Combat-Related Posttraumatic Stress Disorder. (2nd July 2020) - Stolee, Jason D.; Hoyt, Tim; Brinton, Chauncy T.
Abstract: This brief report reviews preliminary data on the utility of a four-session coping skills group for symptoms of Posttraumatic Stress Disorder (PTSD) in an active duty population. While a concerning number of active duty service members return from deployments with posttraumatic stress presentations, treatment engagement and retention can be difficult to attain. To address treatment engagement concerns, a brief psychoeducational group was developed and implemented. Results of this retrospective analysis indicate that the group was experienced as tolerable to a subset of patients, as enrollees endorsed a willingness to recommend the group to peers, and a slight majority completed the group. Moreover, participants who completed the group experienced a statistically significant decrease in PTSD symptoms. While only 20% of enrollees experienced clinically significant improvement in reported PTSD symptoms, this was superior to a matched sample of patients engaged in individual treatment only. This brief group may serve as an addition to current treatment regimens, though limitations indicate that further research and development is warranted.